Food crisis and export taxation: The cost of noncooperative trade policies - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
Export restrictions are trade measures that are permanently adopted by countries throughout the world.1 Piermartini (2004) noted that approximately one-third of World Trade Organization (WTO) members impose export duties. Examples are export taxes implemented by Indonesia on palm oil, by Madagascar on vanilla, coffee, pepper, and cloves, by Pakistan on raw cotton, by the Philippines on copra and coconut oil, by Indonesia on palm oil, and by the European Union on wheat (Bouët and Laborde 2010; OECD 2010). What are the effects of such policy measures? And why do governments restrict exports in times of food crisis?